Spiritual intelligence of its application in modern marketing (Scientific Journal of Research Studies in Future Management, 2024)
The aim of this study was to investigate the application of spiritual intelligence in modern marketing .the research method is practical and correlation .the statistical population of this study includes all customers of a knowledge - based company in the software. according to the unlimited population size using simple random sampling and cochran formula , 384 persons were selected as the sample size .the data collection tool was king 's spiritual intelligence questionnaire ( 2008 ) and the new marketing of Andrews and smith ( 2009 ) .to analyze the data , t - test and Pearson and software spss software were used .the findings showed that there is a positive and significant relationship between spiritual intelligence components ( moral values , social responsibility , and spiritual goal ) and new marketing.